Effectiveness of web-based education program on knowledge, coping, burden, and quality of life among colorectal cancer caregivers in Vietnam: a quasi-experimental study - Hien Thi Nguyen; Hsiu-Hsin Tsai; Hong Thuy Phuong Huynh; Thuy Khanh Linh Tran; Tuan Anh Le; Li-Chueh Weng; Ching-Yu Cheng; Pei-Kwei Tsay; Wann-Yun Shieh; Chia-Yih Liu (BMC Nursing)
Abstract Background Web-based interventions have been acknowledged as a valuable resource in managing caregiving duties, enhancing coping abilities, and improving quality of life (QoL), thereby alleviating burden and mitigating stress. The aim of this study is to examine the effectiveness of a web-based education program on the knowledge, coping strategies, burden, and QoL of caregivers of patients with colorectal cancer. Method A quasi-experimental design was conducted in two randomly selected hospitals. The experimental and control groups consisted of 62 and 65 participants, respectively. The experimental group underwent a web-based education program (WBEP) for 12 weeks and received regular care, and the control group received only regular care. Data were gathered at four intervals: baseline and then 3, 6, and 12 weeks from baseline. Generalized estimating equations were used to understand the effectiveness of the treatment. Results Compared to the mean scores in the control group, those in the experimental group for dysfunctional coping significantly decreased at 6 (14.96 ± 6.57) and 12 weeks (13.92 ± 6.46); emotion-focused coping also significantly declined at 3 (20.52 ± 7.54), 6 (17.25 ± 8.91), and 12 weeks (15.91 ± 8.69); and burden scores were significantly lower at 12 weeks (16.01 ± 10.63). Conclusions The WBEP demonstrated a positive effect on the experimental group in decreasing the use of emotion-focused coping, dysfunctional coping, and burden of care for caregivers but not on knowledge and QoL. The results indicate that healthcare professionals should recognize that a WBEP is an effective method by which medical professionals can engage with and provide support to the caregivers of cancer patients.